Children's physiological and behavioural response evoked by the observation, olfaction, manipulation, and consumption of food textures. Part 1: Liquid products. (March 2023) - da Quinta, N.; Baranda, A.; Ríos, Y.; Llorente, R.; Naranjo, A.B.; Martinez de Marañón, I.
Graphical abstract: Highlights: Thinner liquids were more liked by schoolchildren and evoked a more positive emotional response compared to thicker liquids. Different implicit and explicit responses were measured in schoolchildren during the observation, olfaction, manipulation, and consumption of liquid textures. The codification of the action units located in the upper side of the face was a good approach to prevent artifacts caused by the consumption of foods. Abstract: Children are thought to prefer homogeneous and simple textures that are easy to manipulate in the mouth. Although scientific research has been done on children's acceptance for food textures, there is a lack of knowledge regarding the emotional response elicited by textures in this group of population. Physiological and behavioural methods could be an appropriate approach to measure food-evoked emotions in children since they require a low cognitive effort and allow a real-time measure. In this regard, a study that combined the measure of skin conductance response (SCR) and facial expressions was conducted: (i) to provide a first insight into food-evoked emotions induced by liquid food products that only vary in texture, (ii) to capture the emotional response evoked by the observation, olfaction, manipulation, and consumption of the products, and (iii) to overcome methodological drawbacks that are frequently associated to these methods. To achieve these goals, 50 children (5–12 yrs old) evaluated three liquids designed to only vary in texture (from slightly thick to extremely thick), following four sensory tasks: observation, olfaction, manipulation, and consumption. After each sample was tasted, children rated liking with a 7-pt hedonic scale. Facial expressions and SCR were monitored during the test, and they were analysed as action units (AUs) and basic emotions as well as changes in SCR. Results showed that the extremely thick liquid was less liked by the children and induced a more negative emotional response, whereas the slightly thick liquid was more liked and evoked a more positive emotional response. The combined method used in this study showed good discrimination ability among the three samples tested, obtaining the best discrimination during the manipulation task. The codification of the AUs located in the upper side of the face allowed us to measure the emotional response evoked by the consumption of the liquids, without the artifacts caused by the oral processing of the products. This study provides a child-friendly approach to be used during the sensory evaluation of food products in a broad range of sensory tasks minimising the methodological drawbacks.